External load in male professional volleyball: A systematic review - Marcel Frezza Pisa; Arthur Marques Zecchin; Leonardo Gaspar Gomes; Enrico Fuini Puggina (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. The objectives of this systematic review were to identify the volleyball external loads values in the literature and to verify the applicability of different means of quantification and monitoring of these variables during training sessions and matches. Material and methods: This systematic review was produced following the PRISMA statement recommendations, and the search for publications was carried out in the databases PubMed/NCBI, SportDiscus via EBSCOhost, SciELO. 12 studies meet the criteria and were included in this review. Results: The most used tool for quantification, monitoring and evaluation of external loads are video recording and manual or semi-automatic counting of jumps and distance covered and, more recently, the use of inertial measurements unit. The middle blocker has the highest high jump load, outside hitters jump closer to the maximum more often and setters have a high demand of medium height jumps. Conclusions: Match and training jump loads seem to be similar, and sessions that involve block or attack have a higher jump load. In professional male volleyball, training is planned with variation in training loads according to the period of the sea-son and according to the days of the week before and after games.